Organoleptic and Nutritions Observation of Monosodium Glutamate (MSG)-Free Instant Noodle Seasoning With Soto Padang - Nika Rahma Yanti; Daimon Syukri; Feri Arlius; Khandra Fahmy; Ririn Fatma Nanda (Universitas Dr Soetomo, 2023)
This research is an exploratory study. In this study, instant noodle seasoning was made from natural spices, without the addition of synthetic flavorings and preservatives. If monosodium glutamate (MSG) is consumed beyond the limit and consumed continuously for a long period of time, it will cause various side effects. MSG consumed by someone who cannot tolerate more than 3g/day can have adverse health effects. The purpose of this research is to develop Padang Soto flavored instant noodles using natural spices and without using synthetic flavoring Monosodium Glutamate (MSG). In this study, 4 formulas were made, coded as formula 1, formula 2, formula 3 and formula 4. The results showed that the panelists' preference for the color of instant noodles in formula 4 was 4.05. The panelists' favorite score for the aroma of instant noodle seasoning is highest in formula 4, which is 3.95. As for the taste results obtained, it is known that the panelists' favorite score for the taste of instant noodle seasoning is highest in formula 4, namely 4.05. From the results of the research, a dry seasoning with the code formula 4 has been produced that is delicious based on organoleptic analysis which can be used as a seasoning for instant noodle food products with instant Padang soup flavor. for proximate analysis, the best is also in formula 4, obtained water content of 3.85%, ash content of 1.66%, fat content of 1.29%, and protein content of 7.39%.